A hospital based study to evaluate etiology and epidemiology of occupational corneal foreign bodies (Panacea Journal of Medical Sciences, 2024)
Context: Occupational injuries to eye are very common. Corneal foreign bodies (CFB) are common occupational eye injury. Studies on corneal foreign bodies due to occupational exposure are ignored in developing countries like India.Aims: Our study objective was to determine various occupations related to corneal foreign bodies and demographics, level of education and awareness of patients presenting with CFB acquired during occupational work.Settings and Design: A hospital based cross sectional study at a tertiary hospital at Pali, Rajasthan.Materials and Methods: Patients presenting with CFB were asked about their occupation, level of education, awareness about complications of CFB and use of protective equipments at workplace.Results: We examined total 62 patients with CFBs. All patients were male. 34% were in the age group of 18-29 yrs and 58% were in the age group of 30-45 yrs. Metal work industry was responsible for 29% of presentations and construction work industry for 26% of cases. Only 18% were using protective equipments during occupational activity. 58% patients attempted self-removal of foreign body.Conclusion: CFBs are common among various occupations. The sufferers are commonly young males who are poor and have low education. This occupational hazard can have blinding complications and is generally overlooked. Awareness regarding protective measures must be increased and access to eye care hospital must be increased.